A survey on the factors influencing the pattern of medicine's use: Concerns on irrational use of drugs - Fatemeh Soleymani; Fariba Ahmadizar; Alipasha Meysamie; Mohammad Abdollahi (Wolters Kluwer Medknow Publications, 2013)
Objective: Pharmacists have a remarkable role in rational use of drugs by dissemination of drug information to guide patients, physicians, and policy makers. The present study was undertaken to evaluate the pharmacists' view point about the main factors affecting current drug use pattern regarding rational drug use and the most effective strategies for improving and promoting rational drug use among pharmacists. Methods: In a cross-sectional survey, pre-designed questionnaires were filled in convenient sampling by pharmacists who had attended the congress of rational drug use in Tehran, Iran. Findings: A total of 144 pharmacists with the average age of 40.78 years old were enrolled to the study. Data indicated that the most priorities in irrational use of drugs from pharmacists' view point were lack of appropriate cooperation and communication between physicians and pharmacists (39%), pharmacists' low tariff and economic issues (34%), lack of public knowledge about drug usage (45%), and lack of supervisory regulations on pharmacy practice (15.8%). Conclusion: In this study, lack of public knowledge and awareness about appropriate use of medicines was the most important element from pharmacists' viewpoint in occurrence of irrational drug use. Dissemination of information and compiling of diverse strategies in education, management, regulation, and finance can be very efficient due to a strong relationship between drug policies and performance of regulations and supervisions as well as drug services.